2010
DOI: 10.1016/j.jfluchem.2009.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Separation of fluorinated amino acids and oligopeptides from their non-fluorinated counterparts using high-performance liquid chromatography

Abstract: Chromatographic conditions for the separation of fluorinated amino acids and oligopeptides from their non-fluorinated counterparts were explored. The separation of six pairs of analytes, including both aromatic and aliphatic fluorocarbons, was investigated at various temperatures using both hydrocarbon and fluorocarbon columns and eluents. Our results show that when hydrocarbon eluents are used, fluorocarbon column provides better separation of fluorinated amino acids or oligopeptides from their non-fluorinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…To this end, we resort to statistical descriptors of retention and separation, as outlined in our previous publication [4a]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we resort to statistical descriptors of retention and separation, as outlined in our previous publication [4a]. …”
Section: Resultsmentioning
confidence: 99%
“…In a previous study on the separation of amino acids and proteins (non-fluorinated) [4], we found that optimal analyte separation is achieved by pairing a fluorinated column (F-column) with a hydrogenated eluent (H-eluent) or a hydrogenated column (H-column) with a fluorinated eluent (F-eluent), i.e., hetero-pairing of the column and the eluent. Fluorinated eluents have been reported to induce unique selectivity on nonfluorinated analytes, which was attributed to the adsorbed solvent molecules, 2, 2, 2- trifluoroethanol, on the stationary phase surface [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorous solvents are typically very nonpolar and usually cannot be used in reversed-phase LC. However, because TFE can be miscible with many organic solvents, it has been utilized as a controllable solvent for the elution of fluorinated compounds in fluorous and reversed-phase LC [20,21]. Furthermore, we screened the retention behavior of the derivatives on several commercially available fluorous LC columns: Fluorous LC column are commercially available: examples include Fluophase RP (Thermo Fisher Scientific, San Jose, CA, USA), Fluofix-II 120E (Wako Pure Chemicals, Osaka, Japan), and (Fig.…”
Section: Selective Analysis Of Biogenic Primary Amines Using Lc-ms/msmentioning
confidence: 99%
“…Fluorine incorporation helps to block the metabolism and increase the bioavailability and efficacy of pharmaceuticals [2][3][4][5]. The chromatographic separation of closely related species coming from the synthesis of organofluorine compounds enables research in this area, but the separation of mixtures of closely related fluorination isomers and the separation of fluorine-containing drugs from their desfluoro analogs can be challenging [6][7][8][9][10][11], owing to the close structural similarities and small differences in physical properties between desired and undesired components.…”
Section: Introductionmentioning
confidence: 99%